The business cycle in a changing world - Burns, Arthur F.; National Bureau of Economic Research (New York : National Bureau of Economic Research; distributed by Columbia University Press, 1969)
The essays in this volume draw upon the research and thinking of an economist who has devoted his life to study of the nature and cause of prosperity and depression.
"Essays reprinted to honor Dr. Burns for his 38 years of active involvement in the research and administration of the National Bureau of Economic Research and on the occasion of his election as honorary chairman of the bureau's Board of Directors."
Includes bibliographical footnotes and index.
rpm 25/01/2019
Loans
Keywords: Business cycles